DRS // CUMULUS Oslo 2013. The 2nd International Conference for Design Education Researchers - Nielsen, Liv Merete (FormAkademisk, 2013)
14-17 May 2013, Oslo, Norway We have received more than 200 full papers for the 2nd International Conference for Design Education Researchers in Oslo. This international conference is a springboard for sharing ideas and concepts about contemporary design education research. Contributors are invited to submit research that deals with different facets of contemporary approaches to design education research. All papers will be double-blind peer-reviewed. This conference is open to research in any aspect and discipline of design education Conference theme Design Learning for Tomorrow - Design Education from Kindergarten to PhD Designed artefacts and solutions influence our lives and values, both from a personal and societal perspective. Designers, decision makers, investors and consumers hold different positions in the design process, but they all make choices that will influence our future visual and material culture. To promote sustainability and meet global challenges for the future, professional designers are dependent on critical consumers and a design literate general public. For this purpose design education is important for all. We propose that design education in general education represents both a foundation for professional design education and a vital requirement for developing the general public’s competence for informed decision making. REGISTRATION AT http://www.hioa.no/DRScumulus